Educational research : - Gay, L. R. (Prentice Hall, 2008)
This market leader focuses on both "how to do" and "how to read research" helps teachersnbsp;become competent consumers and producers of educational research. nbsp;Accessible writing style and light, humorous tone help demystify this demanding topic.nbsp; nbsp; Uses a direct, step-by-step approach to thenbsp;research processnbsp;and incorporates tasks and articles throughout to provide teachers with the practice they need to master research steps and evaluation.